Crystal Growth in the Combustion Synthesis of α‐Si3N4 Using Si with Different Particle Sizes. Issue 10 (28th July 2015) - Ge, Yiyao; Wang, Qi; Cui, Wei; Zou, Yifeng; Xie, Zhipeng; Chen, Kexin
Abstract : In this present work, Si3 N4 powders with high α‐phase contents and distinct crystal morphologies were prepared via a promising approach of combustion synthesis (CS), using Si powders with different particle sizes as reactants. The influence of Si particle size on phase composition and crystal morphologies in the products was systematically investigated. Two unique crystal morphologies, radial‐spheroidal‐cluster and flowerlike, were observed in the Si3 N4 products. The crystal growth mechanisms of Si3 N4 granules in the CS system with disparate Si have been proposed based on experiments and thermokinetic calculations. As conclusion, the α‐phase content in the final product was synergetically dominated by the vaporization process of Si particles and the α–β phase transformation of Si3 N4 during the after‐burn period. Si3 N4 powders with high α‐phase content can be obtained from Si powders with an appropriate particle size.